Psychoanalytic Perspectives on Psychopathy in Liz Jensen's the Ninth Life of Louis Drax (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Psychopathy is a complex psychological disorder that arises from the interaction of genetic and environmental elements. Individuals with psychopathy are characterized by lack of empathy, manipulation of others, impulsivity, and antisocial behavior. The environment plays a crucial role in the development of this disorder. In Liz Jensen's novel The Ninth Life of Louis Drax, psychopathy and psychological problems are presented in an accurate and realistic way, providing ideal conditions for understanding these psychological problems. The author successfully shows the effect of psychological issues on family and social life, which raises awareness about it. This paper discusses the psychological issues in the novel in details.